Statue of Charity, Frere temple - Ghosh, Ayan (2023)
The Frere Temple originally housed a bust of Lady Frere, which was defaced by vandals. The damaged bust was sent to England but was beyond repair. In its place, a bronze statuary sculpted by English sculptor Herbert Hampton (1862–1929) was installed. The statue is mistakenly identified as Queen Victoria, because of its location in (former) Victoria Gardens.